Risk assessment of plant food supplements and other herbal products containing aristolochic acids using margin of exposure (MOE) approach - Abdullah, Rozaini; Diaz, Leolean Nyle; Wesseling, Sebastiaan; Rietjens, Ivonne M. C. M. (Taylor & Francis Group, 2016)
After the incidences of induction of aristolochic acid nephropathy after consumption of herbal weight loss preparations that accidentally contained aristolochic acids (AAs), several countries defined national restrictions on the presence of AAs in food, including plant food supplements (PFS) and herbal products. This study investigates whether the risks associated with exposure to AAs via PFS and herbal products are at present indeed negligible. Data reported in literature on AA levels in PFS and other herbal products and also obtained from a new series of PFS in the present study were used to calculate the estimated daily intakes (EDIs) and corresponding margins of exposure (MOEs). Available literature data revealed that 206 out of 573 samples were found to contain aristolochic acid I (AAI) and/or aristolochic acid II (AAII). The results obtained from recently collected PFS revealed that both AAI and AAII were detected in three out of 18 analysed PFS at levels up to 594.8 and 235.3 µg g-1, respectively, being in line with the levels reported in literature. The EDIs resulting from intake of these PFS resulted in MOEs that were generally below 10,000, corroborating the priority for risk management. Although these results refer to PFS collected by targeted sampling strategies, the data reveal that AA-containing PFS are still freely available. When considering that the use of these samples may be limited to shorter periods of time, the EDIs might be lower, but MOE values would still be lower than 10,000 for more than 50% of the AA-containing PFS and herbal products. In conclusion, the presence of AAs in PFS and herbal products even several years after instalment of the legal restrictions still raises concern, especially for people who frequently use the respective PFS and herbal products.